Design, synthesis and biological evaluation of novel pyrazinone derivatives as PI3K/HDAC dual inhibitors. (15th November 2022) - Wang, Zi-Xiao; Wang, Shuai; Qiao, Xue-Peng; Li, Wen-Bo; Shi, Jian-Tao; Wang, Yi-Ru; Chen, Shi-Wu
Graphical abstract: Research highlights: Some pyrazin-2( 1H )-ones as PI3Kα/HDAC6 dual inhibitors were synthesized and identified. Compound 9q promotes the acetylation of α-tubulin, and blocks the PI3K/AKT/mTOR signal way in MV4-11 cells. Compound 9q induces MV4-11 apoptosis and arrested cell cycle in G2/M phase. Compound 9q simultaneously well binds to both of PI3Kα and HDAC6. Abstract: PI3Ks and HDACs play essential roles in the occurrence and progression of leukemia. Herein, a series of novel pyrazin-2(1 H )-one derivatives were rationally designed and synthesized as novel dual PI3K and HDAC inhibitors based on scaffold replacement and heterozygous strategies. Most of the target compounds showed potent inhibitory potency to PI3Kα and HDAC6. Especially, compound 9q displayed PI3Kα and HDAC6 inhibitory with IC50 values of 372 nM and 4.5 nM, and anti-proliferative activity against MV4-11 cells with IC50 value of 0.093 ± 0.012 μM. Further mechanistic studies revealed that 9q induced apoptosis, arrested the cell cycle in the G2/M phase, promoted the acetylation of α-tubulin, and blocked the PI3K/AKT/mTOR signal way in MV4-11 cells. All the results demonstrated that 9q was a promising lead candidate for further development of novel PI3K/HDAC dual inhibitors for leukemia treatment.